Comparative characteristics of BRICS and the SCO and their place on the world stage - Кошелєва, Христина (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
The article by Kristina Kosheleva «Comparative characteristics of BRICS and the SCO and their place on the world stage» presented results of study of SCO and BRICS and comparative characteristics of their areas. BRICS (BRICS) isthe international group, which includes five of the most rapidly developing countries such as Brazil, Russia, India, China, South Africa. The five countries occupya quarter of the Earth's surface, 40% of the world population and 15% of world trade. In turn Shanghai Cooperation Organization now covers large area of the Asian continent.Unlike SCO, BRICS is not an international intergovernmental organization. It is not based on its articles of incorporation.  As for  BRICS and SCO the general direction stands the activity in the economic sphere. Representatives of countries regularly participate in various interstate initiatives to discuss the most pressing issues of the world economy and world politics.  Countries of BRICS and SCO are trying to enhance cooperation in the field of education. BRICS emphasize the importance of education as well as efficiency and social importance of investment in this sector. SCO created its university, which received the first students - Masters in September 2010. In addition to strengthening their positions in the IMF, countries in BRICS are trying to strengthen their influence in the UN and OECD. The activity of the Shanghai Cooperation Organization in Central Asian region overlaps with the activities of many international organizations in their main directions.